Conscientious objection and induced abortion in Europe. (August 2013) - Heino, Anna; Gissler, Mika; Apter, Dan; Fiala, Christian
ABSTRACT The issue of conscientious objection (CO) arises in healthcare when doctors and nurses refuse to have any involvement in the provision of treatment of certain patients due to their religious or moral beliefs. Most commonly CO is invoked when it comes to induced abortion. Of the EU member states where induced abortion is legal, invoking CO is granted by law in 21 countries. The same applies to the non-EU countries Norway and Switzerland. CO is not legally granted in the EU member states Sweden, Finland, Bulgaria and the Czech Republic. The Icelandic legislation provides no right to CO either. European examples prove that the recommendation that CO should not prevent women from accessing services fails in a number of cases. CO puts women in an unequal position depending on their place of residence, socio-economic status and income. CO should not be presented as a question that relates only to health professionals and their rights. CO mainly concerns women as it has very real consequences for their reproductive health and rights. European countries should assess the laws governing CO and its effects on women's rights. CO should not be used as a subtle method for limiting the legal right to healthcare.